2022
DOI: 10.3390/biom12010067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proteases and Serpin Protease Inhibitors in β-Cell Biology and Diabetes

Abstract: Regulation of the equilibrium between proteases and their inhibitors is fundamental to health maintenance. Consequently, developing a means of targeting protease activity to promote tissue regeneration and inhibit inflammation may offer a new strategy in therapy development for diabetes and other diseases. Specifically, recent efforts have focused on serine protease inhibitors, known as serpins, as potential therapeutic targets. The serpin protein family comprises a broad range of protease inhibitors, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The inactive serine protease inhibitor complex was highly stable and made serine protease inactive. Thus, the Serpins inhibition mechanism is “suicide,” and each serpin molecule is “single-use.” ( 20 ) Serpina3c has leucine at the P1 position flanked by phenylalanine and threonine at P4-P4’. The scissile bond is formed between leucine and serine at position P1-P1’, which is consistent with the structure of SerpinA3 at this site ( 21 )( Figure 1B ).…”
Section: Homology and Molecule Features Of Serpina3cmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactive serine protease inhibitor complex was highly stable and made serine protease inactive. Thus, the Serpins inhibition mechanism is “suicide,” and each serpin molecule is “single-use.” ( 20 ) Serpina3c has leucine at the P1 position flanked by phenylalanine and threonine at P4-P4’. The scissile bond is formed between leucine and serine at position P1-P1’, which is consistent with the structure of SerpinA3 at this site ( 21 )( Figure 1B ).…”
Section: Homology and Molecule Features Of Serpina3cmentioning
confidence: 99%
“…Serpins represent the largest and most versatile family of protease inhibitors, and its name comes from the function that the family was first described, which is serine protease inhibitor. Most serine protease inhibitors inhibit serine proteases (such as chymotrypsin, trypsin, and elastase), thus inhibiting the cascade of proteolysis and participating in physiological processes such as coagulation, inflammation, complement activation, and fibrinolysis ( 20 , 33 , 34 ). At present, it has been shown that the molecular function of Serpina3c is to act as a serine protease inhibitor, and is capable of binding to and inhibiting the activity of a wide range of serine proteases, including Cathepsin G and thrombin.…”
Section: Molecular Function Of Serpina3cmentioning
confidence: 99%
“…The activity of proteases appears to play a key role in the survival of multicellular organisms. These enzymes are responsible for breaking peptide bonds, which in turn leads to irreversible post-translational modifications of proteins [ 32 ]. An example of such proteolytic cascades is inflammation and coagulation, which, if inappropriately activated, can lead to clotting disorders and inflammation in the host.…”
Section: Introductionmentioning
confidence: 99%
“…This issue focuses on the molecular mechanisms that control beta cell mass expansion and survival, particularly emphasising significant pathways for mature beta cell function. The contributions cover a broad range of topics, including the impact of oxidative stress on beta cells [ 1 , 2 , 3 ], inter-tissular communication [ 4 , 5 , 6 , 7 ], and master regulators of beta cell mass and function [ 8 , 9 , 10 ], among others.…”
mentioning
confidence: 99%
“…The authors emphasize the importance of an early and accurate diagnosis of diabetes in these contexts. Kryvalap and colleagues [ 7 ] review the impact of proteases expressed in the exocrine pancreas and serpin protease inhibitors on islet pathophysiology. The authors explore opposing views on the inhibition or augmentation of protease activity in pancreatic islet biology and inflammation and discuss the potential therapeutic targeting of serpins for tissue regeneration and inflammation inhibition in the context of islet dysfunction.…”
mentioning
confidence: 99%